2014
DOI: 10.3389/fpls.2014.00404
|View full text |Cite
|
Sign up to set email alerts
|

Capturing sequence variation among flowering-time regulatory gene homologs in the allopolyploid crop species Brassica napus

Abstract: Flowering, the transition from the vegetative to the generative phase, is a decisive time point in the lifecycle of a plant. Flowering is controlled by a complex network of transcription factors, photoreceptors, enzymes and miRNAs. In recent years, several studies gave rise to the hypothesis that this network is also strongly involved in the regulation of other important lifecycle processes ranging from germination and seed development through to fundamental developmental and yield-related traits. In the allop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 56 publications
2
87
0
1
Order By: Relevance
“…Although targeted capture has primarily been applied to protein-coding exons (Hodges et al 2007), regulatory regions such as UTR, miRNA, promoter regions, and other non-coding elements can also be targeted in a highly parallel fashion (Bainbridge et al 2011; Hebert et al 2013; Linnen et al 2013; Carneiro et al 2014a; Carneiro et al 2014b; Schiessl et al 2014). In addition, non-coding regions flanking exons and other baited regions are often indirectly targeted (Samuels et al 2013).…”
Section: Targeted Capture Without a Reference Genomementioning
confidence: 99%
See 1 more Smart Citation
“…Although targeted capture has primarily been applied to protein-coding exons (Hodges et al 2007), regulatory regions such as UTR, miRNA, promoter regions, and other non-coding elements can also be targeted in a highly parallel fashion (Bainbridge et al 2011; Hebert et al 2013; Linnen et al 2013; Carneiro et al 2014a; Carneiro et al 2014b; Schiessl et al 2014). In addition, non-coding regions flanking exons and other baited regions are often indirectly targeted (Samuels et al 2013).…”
Section: Targeted Capture Without a Reference Genomementioning
confidence: 99%
“…Finally, the uniformity in coverage across targeted loci may be leveraged to infer copy number variation (CNV) based on relative coverage (Saintenac et al 2011; Schiessl et al 2014; Jiang et al 2015). The utility of targeted capture in this respect is a tremendous advantage because structural variation (e.g., whole genome or gene duplications and chromosomal rearrangements) can play an important role in adaptation and speciation (Lowry & Willis 2010; Kondrashov 2012), yet identifying and characterizing structural variation is often difficult.…”
Section: Targeted Capture Without a Reference Genomementioning
confidence: 99%
“…Due to genome triplication and alloploidization of B. napus, three homologs from each ancestor genome can theoretically be expected, but in average there are 4.4 functional gene copies present (Parkin et al, 2010). Variation of the gene copy number in B. napus was previously reported for several proteins, such as proline dehydrogenase (Faes et al, 2014), cytokinin receptors (Kuderova et al, 2015), and flowering-time regulatory genes (Schiessl et al, 2014). In the process of polyploidization, B. napus has undergone a high degree of genome and gene duplications and genome rearrangements (Zmienko et al, 2014), including homoeologous recombination, which leads to gene copy variation and presence/absence variation (Gaeta and Chris Pires, 2010;Udall et al, 2006).…”
Section: Discussionmentioning
confidence: 73%
“…The high number of homologous genes leads to higher robustness against mutation and loss of function risks (Bekaert et al, 2011) and a better adaption to the environment (Chen, 2010). Simultaneous transcription enables a faster and increased reaction capacity and a better fine tuning in physiological pathways (Schiessl et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On average, 4.4 expressed gene copies in B. napus have been identified genome-wide for every Arabidopsis gene (Parkin et al 2010). However, Lloyd et al (2014) observed that genes involved in meiosis tend to be retained in single copies after polyploidisation, while Schiessl et al (2014) found additional duplication/deletion events between the A and C genomes of B. napus also influenced gene copy number. A probable effect of human-directed genomic selection was also observed by Chalhoub et al (2014): all glucosinolate catabolism gene copies were retained in B. napus from diploid B. rapa and B. oleracea, putatively as a result of selection for low glucosinolates in this domesticated crop species.…”
Section: Proximity To Model Plant a Thalianamentioning
confidence: 99%